PENGARUH KOMPETENSI, MOTIVASI DAN KECERDASAN EMOSI TERHADAP KINERJA DOSEN DI PERGURUAN TINGGI SWASTA KOPERTIS WILAYAH II (STUDI KASUS PADA UNIVERISTAS BINADARMA DAN UNIVERSITAS TRIDINANTI) - FAITULLAH . (Program Studi Magister Manajemen FE Unsri, 2014)
The study entitled â€œThe Influence of Competency, Motivation, and Emotional Intelligence on the Performance of the Lecturers at the Private Universities Within Kopertis Wilayah II Palembang is carried out with the objective of revealing the magnitude of the influence of competency, motivation, and emotional intelligence both partially and simultaneously on the performance of the lecturers at the Private Universities within Kopertis Wilayah II Palembang. The study is triggered by the fact that the performances of some lecturers have not satisfied the expectation of the Law No. 14 of the Year 2005 about Teachers and Lecturers, especially in the field of research and dedication to the public. This is a quantitative study involving 97 respondents.Â The regression test is used after the testing of classical assumption and the test of validity/reliability. The result of the study as a whole shows that the performance of 61.7% the lecturers at Kopertis Wilayah II Palembang is influenced by competency, motivation, and emotional intelligence; whereas the performance of rest of the lecturers, 38.7% is influenced by other factors (organizational culture, leadership, and etc.) outside this study. Some suggestions are proposed in this study as follows: The competency of the lecturers should be improved in the future.; The Presidents of the Private Universities within Kopertis Wilayah II Palembang should motivate the lecturers at their universities to be willing to carry out the Thidharma of Higher Education, especially in the field of research.; And the emotional intelligence of the lecturers at the Private Universities within Kopertis Wilayah II Palembang should be improved through the ESQ training.